PENGEMBANGAN SISTEM EVALUASI PEMBELAJARAN PAI BERBASIS MULTIKULTURAL DALAM PERSPEKTIF MODERASI BERAGAMA - M. Debi Wananda; M. Ridlwan Al-Khoir; M. Hasyim Asyari; Askhabul Kirom (Journal Multicultural of Islamic Education, 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping the character of students in Indonesia's diverse society. However, evaluation of PAI learning has so far focused primarily on cognitive aspects such as memorization and mastery of material, while aspects of attitude, tolerance, and religious moderation have not received adequate attention. This situation has resulted in the values ​​of diversity and respect for differences not being fully internalized in the learning process. This study aims to describe and analyze the development of a multicultural-based PAI learning evaluation system from a religious moderation perspective. The study employed library research with a historical-philosophical approach and content analysis techniques. Data sources were obtained from regulations, books, and scientific journals relevant to the research theme. The study results indicate that development of PAI evaluation needs to be carried out through a reorientation of evaluation objectives, integration of multicultural values ​​into learning materials, diversification of assessment instruments, strengthening the role of teachers, and creating an inclusive school culture. Thus, PAI evaluation measures not only knowledge but also students' attitudes and behaviors in respecting diversity and applying the values ​​of religious moderation in daily life.